High Concentration of Dezocine Induces Immune Escape of Lung Cancer and Promotes Glucose Metabolism through Up-Regulating PD-L1 and Activating the NF-ΚB Pathway - Dong, Weiping; Zhang, Dong; Zhu, Aiyun; Hu, Yanli; Li, Wei (Current Molecular Medicine, 2022)
Background: Dezocine is an opioid analgesic that can affect the immune system. Here, we explored the synergy of high concentration of Dezocine and programmed death-ligand 1 (PD-L1) with regards to immune escape and glucose metabolism in lung cancer (LC). Methods: PD-L1 level in human LC cell lines was determined and the influence of Dezocine at different concentrations for the proliferation of LC cells was identified. Next, LC cells were transfected to alter PD-L1 level, and exposed to Dezocine at 8 μg/mL to explore their effects on cell proliferation, production of interferon-γ (IFN-γ), contents of glucose, lactate, and NADPH/NADP+, and activation of the nuclear factor-ΚB (NF-ΚB) pathway. Results: PD-L1 level was increased in LC cells and Dezocine (8 μg/mL) impaired the proliferation of LC cells. Down-regulating PD-L1 inhibited cell proliferation, enhanced production of IFN-γ, and reduced the contents of glucose, lactate, and NADPH/NADP+, while up-regulating PD-L1 caused the opposite results. Dezocine (8 μg/mL) induced immune escape and glucose metabolism in LC, and Dezocine-induced effects were reversed by down-regulating PD-L1. Dezocine (8 μg/mL) up-regulated PD-L1 by activating the NF-ΚB pathway. Conclusion: Dezocine at 8 μg/mL promotes immune escape and glucose metabolism in LC through up-regulating PD-L1 and activating the NF-ΚB pathway.
Keywords: nuclear factor-ΚB pathway